The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1007/s00405-013-2614-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measurement of m-RNA levels to assess expression of cyclooxygenase-II, inducible nitric oxide synthase and 12-lipoxygenase genes in middle ear cholesteatoma

Abstract: To assess expression of three main inflammatory genes, COX-II, ALOX-12 and i-NOS, quantitatively at transcriptional level in cholesteatoma matrix tissue. Ten patients who have chronic otitis media with primary acquired cholesteatoma were included in this study. Tissue samples obtained from cholesteatoma matrix and external ear canal skin (control tissue). Expression of the targeted genes (COX-II, i-NOS and LOX-12) was assessed using real-time quantitative polymerase chain reaction (RT-PCR) technique. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Consistent with our observations, Lee et al (27) did not see a significant change in the iNOS expression in cholesteatoma ears. In contrast, Çatli et al (11) reported a lower expression of iNOS in cholesteatoma ears. It is important to recognize that in the studies of Lee et al (27) and Çatli et al (11), cholesteatoma matrix was compared with controls from skin in the ear canal, whereas in our study the middle ear mucosa was targeted.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Consistent with our observations, Lee et al (27) did not see a significant change in the iNOS expression in cholesteatoma ears. In contrast, Çatli et al (11) reported a lower expression of iNOS in cholesteatoma ears. It is important to recognize that in the studies of Lee et al (27) and Çatli et al (11), cholesteatoma matrix was compared with controls from skin in the ear canal, whereas in our study the middle ear mucosa was targeted.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast, Çatli et al (11) reported a lower expression of iNOS in cholesteatoma ears. It is important to recognize that in the studies of Lee et al (27) and Çatli et al (11), cholesteatoma matrix was compared with controls from skin in the ear canal, whereas in our study the middle ear mucosa was targeted. The associations between OME and cholesteatoma and other types of chronic otitis media imply that the answer to the enigma of cholesteatoma would probably be found within the middle ear (1).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation